Living Constitutions - Gray L. Dorsey (Washington University Law Quarterly, 1955)
A French poet once ranked the arts according to the intractability of the media, rating sculpture highest. By this standard, constitution-making is the highest of all arts because its medium, more stubborn than marble, is what William Faulkner has called the “simple, incorrigible, intractable, invincible human heart.” Simple enough to write a constitution. But what makes it live? This problem, of what it is that quickens a social blueprint into a society, is an intellectual puzzle I have worked at for nine years. I believe the last piece has fallen into place. The present article consists of the first once-over view of the result.
Keywords: Natural law; Peace